Skeletal Metastatic Mimicry in Ovarian Cancer: A Case Report on the Diagnostic Challenges of Osteopetrosis and Metabolic Bone Disease - Shohana, Khandaker Samia; Sultana, Nasreen; Bailey, Shamsun Nahar; Sarkar, Shimul; Bari, A K M Fazlul (Bangladesh Journal of Nuclear Medicine, 2026)
Ovarian carcinoma is a significant malignancy in women, frequently requiring comprehensive follow-up to detect metastasis. Skeletal involvement is often assessed via anatomical imaging like CT and MRI; however, these modalities can occasionally encounter "metastatic mimics." Reported case entails a 43-year-old woman with a history of ovarian cancer whose follow-up contrast enhanced CT (CECT) and magnetic resonance imaging (MRI) suggested widespread osteoblastic metastases. Subsequent functional imaging (bone scintigraphy) and laboratory investigations inclined toward metabolic bone disease rather than malignancy. A CT-guided core needle biopsy of the rib ultimately confirmed the absence of malignant cells, identifying the dense skeletal lesions as a combination of osteopetrosis and severe vitamin D deficiency (osteomalacia). This case highlights the necessity of multimodality imaging and histological confirmation to prevent the misdiagnosis of metastatic disease. Bangladesh J. Nuclear Med. 28(2): 394-398, 2025